INVESTIGATION OF FORMING OF HIGH-RESISTANT COVERINGS, PRODUCED BY TWO-STAGE METHOD - V. I. Savich; O. G. Cherneta; A. N. Korobochka; A. B. Sychkov; A. M. Nesterenko; V. L. Pljuta; M. A. Murikov (Литьë и металлургия)
The regularities of high-resistant coverings forming in surface zone of instrumental steel and hard-alloy insertions for cutting instrument at two-stage method of their production are studied. The prospect of application of the developed method for resistance increase of elements of mining and smelting equipment and internal combustion engine is determined.